RANCANG BANGUN APLIKASI STORYBOARD BERBASIS ANDROID - lim, william; Arnomo, Sasa (Computer Science and Industrial Engineering, 2022)
Storyboard is a collection of image sketches that are arranged by script and make it simpler for users to convey story thoughts. The storyboard describes each step of the film, game, web and animation that will be made, This means that the sketches in the storyboard are more coordinated and when a mistake happens, the users can immediately fix it. Storyboard is the first the term for sketch that contains a thought or story script in succession of every scene. The issue of making storyboards in animation or promotion still using a pencil, paper and must have a PC, with installing Adobe Photoshop and Illustrator which costs a great deal and not everyone has their own PC. The objective is to make it more easier for users to imagine their thoughts and develop their creativity. Make users to understand the plot and content of the story going to tell. The most common way of making sketches can be finished anyplace. The method used in making this application is using the Agile method. The conclusion and results of this storyboard application is that it can assist animator with making more convenience for artists to work on their tasks anyplace and whenever.